Zepp Quiz sebagai Media Pembelajaran Kreatif dalam Meningkatkan Pemahaman Sejarah Kebudayaan Islam Siswa MA - Muhammad Rizqi Bahrain; Jasiah Jasiah (Lembaga Pengembangan Kinerja Dosen, 2026)
This research aims to develop Zepp Quiz as a creative learning media to enhance students' understanding of Islamic Cultural History at Madrasah Aliyah. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The developed product consists of 10 multiple-choice questions about the Conquest of Mecca with varying difficulty levels, equipped with supporting illustrations, educational feedback, point systems, timers, and leaderboards. Data collection was conducted through quantitative methods using validation questionnaires from media experts and material experts with a Likert scale of 1-5. Data analysis was performed descriptively by calculating average scores and feasibility percentages. The results showed that media expert validation obtained an average score of 4.31 or 86% in the very feasible category, while material expert validation obtained an average score of 4.25 or 85% in the very feasible category. Based on expert validation results, Zepp Quiz learning media is declared very feasible to be used as a creative learning media in Islamic Cultural History learning at Madrasah Aliyah.